Arbuscular mycorrhiza associated with Cannabis ruderalis Janisch in foothills of Trans-Ili Alatau (Eurasian Journal of Ecology, 2016)
Studies of plant’s arbuscular mycorrhizas showed that the Cannabis ruderalis Janisch in nature is usually nonmycorrhizal species. But, in some cases there are plant population of this species, that have high level of mycotrophic. So, in one of the plant association of the Ili River’s lower right-bank reaches, reveal that some specimens of cannabis weed had high and medium levels of intensity of mycorrhizal infection. Perhaps, presence of endomycorrhizal fungus structures in the root bark of these plants and high intensity of mycorrhizal infection caused by severe growing conditions of this plantpopulations: dry climate, overgrazing and soil degradation.
Keywords: Cannabis ruderalis Janisch; arbuscular mycorrhiza; intensity of mycorrhizal infection